Evaluation of the Executive Functioning and Psychological Adjustment of Child-to-Parent Offenders: Epidemiology and Quantification of Harm - Fandiño, Ricardo; Basanta, Juan; Sanmarco, Jéssica; Arce, Ramón; Fariña, Francisca (Frontiers in Psychology, 2021)
With the aim of ascertaining if child-to-parent offenders have impairments in the executive functions and psychological maladjustment, and to quantify the potential harm and epidemiology, a field study was designed. As for this, 76 juvenile offenders sentenced for child-to-parent violence were assessed in executive functions (Stroop tasks) and psychological adjustment (Minnesota Multiphasic Personality Inventory-Adolescent, MMPI-A). The results showed valid responses for 75 juveniles and that data were not generally biased in line with defensiveness or malingering (differential diagnosis in justice juvenile evaluations). In psychological adjustment, the results revealed a significantly higher maladjustment among offenders on all the basic clinical scales with 23% more symptoms of hysteria than the normative population, 37% more of depressive symptoms, 44% more of hypochondriac symptoms, 68% more of psychopathic deviation symptoms, 46% more of paranoid symptoms, 26% more of psychasthenic symptoms, 24% more symptoms of schizophrenia, 17% more symptoms of hypomania, and 13% more symptoms of social introversion. Epidemiologically, the prevalence rates of clinical deterioration were significantly greater than expected (0.05 in normative sample) in hypochondria (28.0%), depression (29.3%), hysteria (29.3%), psychopathic deviation (60%), paranoia (30.7%), psychasthenia (22.7%), and schizophrenia (25.3%). As for the cognitive functions, the offenders exhibited impairments estimated at 62.0% in word reading, 47.9% in color naming, 45.8% in color-word, and 11.9% in interference and a significantly higher prevalence of caseness than expected in word reading (65%), color naming (71%), and color-word (70.2%). The implications of the results for intervention are discussed.